Folksonomy in electronic gaming platforms: analysis of popular markers in the roguelike and soulslike genres - Santana, Fernanda Lacerda (2023)
Information retrieval through tags assigned by users in information systems characterizes the use of folksonomy. In this context, studies on representation and retrieval using folksonomy in Information Science have been gaining importance in recent years. Folksonomy in electronic gaming platforms can significantly support the retrieval of existing genres in the gaming industry when tags are assigned. In light of this, this research aims to identify folksonomy in the assignment of popular markers made by users to represent two genres in the universe of electronic games on the Steam platform. As a hypothesis, it proposes that the assignment of tags to represent electronic games results from the collaborative practice of users in assigning markers to games, considering the representational function of the tag. Regarding methodology, it is characterized as descriptive, exploratory research with a qualitative approach, with direct observation. The methodological procedures were divided into three phases (organization of material, treatment of results, inferences, and interpretations). The analysis considered general aspects of popular markers in relation to genres and the presentation of the representational function of tags, organizing them into Identification, Typology, Categorization, and Characterization. As a result, folksonomy was identified through popular markers that refer to the genre's style, gameplay experience, available audiovisual resources, gameplay, and game plot. It was possible to perceive that the community itself that creates the genres can also identify their characteristics. It is concluded that gaming indexing platforms themselves need user-generated representations to aid in the identification process of games and their characteristics.